122k views
0 votes
Elimination/Substitution Method - Make sure to show your work! ♡

1) Elimination: 3x - 2y = -39 , 5x + 2y = -33

2) Use Substitution or Elimination Method: y = -2x + 4 , 3x - 2y = 6

3) Use Substitution or Elimination Method: 2x + 3y = 3 , x + 6y = -3

User Neidy
by
6.2k points

1 Answer

3 votes

Answer: Well, using the elimination process the answer would be,

x=-12

y=3


Explanation:

2) I used substitution, x= 27/11, y= -10/11

3) x= 3, y= -1

GOOD LUCK!


User Mrjmh
by
6.2k points